Motorist-initiated highway incident detection method based on wireless positioning technology - Hang Wen; Li Xuhong; He Jie; Mao Haijun (2008 IEEE International Conference on Automation and Logistics, 2008)
An innovative motorist-initiated incident detection method using wireless positioning technology, such as global positioning system (GPS) and cellular phone positioning system (CPS) is developed. Then, the basic detection algorithm is presented. The position information and operating characteristics of reporting vehicles are detected using wireless positioning system and is transferred by global system for mobile communications (GSM) networks. According to the information, the traffic management center (TMC) can position the incident accurately in short order. The validity of this incident detection method is proved by a simulation model and the detecting performances are evaluated under different traffic and incident conditions.